Structural dependence of magnetic exchange coupling parameters in transition-metal complexes - Melo, Juan Ignacio (2013)
Magnetic exchange coupling parameters are routinely calculated within same structures for high- and low-spin states, neglecting structural relaxations and temperature effects present in measurements. To estimate these effects, we calculate magnetic couplings in a set of transition-metal complexes by relaxing the high-spin and broken-symmetry structures and taking into account the zero-point energies for both spin configurations. Structural relaxations slightly worsen results relative to experimental values, while zero-temperature ro-vibrational effects slightly improve calculated couplings. Because the complexes considered here are the gas-phase structures of the crystal units, our results can be regarded as an upper-bound for relaxation effects in the crystal-phase.